The Study Of Vibration Motion Of Honey Kuih Loyang Mold Frame - Mohamad Hanifah, Mohamad Farhan (Universiti Sains Malaysia, 2018)
Honey Kuih Loyang is getting famous from time to time for its crunch and sweetness. The demand for the biscuits are getting higher mostly during the festive day. The slow production of the biscuits has become as problem to meet the demand. A semi-automatic machine had been designed to solve the problem of late production. However, the designed machine cannot work as effective as the traditional machine. In order to design a semi-automatic machine that can work as effective as the traditional machine, the vibration motion of the mold frame of the traditional machine is studied. The natural frequency and mode shape of the vibration motion should be known. By using modal analysis simulation and fixed support boundary conditions, the first 10 inherent natural frequencies and mode shapes of the vibration motion are evaluated. The natural frequencies are ranging from 165.97 Hz to 740.06 Hz. The mode shapes consists of lateral-torsional and axial bending vibration. 3 different materials which have different mechanical properties are analyzed for the same solid model of mold frame as an alternative to verify the simulation. The results of the simulation from comparing for all the materials shows a good agreement with the available literature results. The simulations are verified.